T2 - judgment day [videorecording (DVD)]. - Cameron, James, 1954-; Furlong, Edward, 1977-; Schwarzenegger, Arnold; Hamilton, Linda, 1956-; Patrick, Robert, 1958- (2009)
The Terminator is back and now he's one of the good guys, sent back in time to protect John Connor, the boy destined to lead the freedom fighters of the future. Special features include a special edition version of the film.